Inside paragraphs typographic fundamentals - Highsmith, Cyrus (Princeton Architectural Press, 2020)
What goes on inside a paragraph of printed text? Cyrus Highsmith's Inside Paragraphs is an essential primer on the basics of typography that focuses specifically on the role of printed text within a paragraph. Engaging full-page illustrations and Highsmith's accessible explanations show the role of white space between letters, words, and lines. Perfect for students and professionals alike, this updated edition includes a new preface.